Prevalence and Clinical Presentations of Dilated Cardiomyopathy in Sudanese patients with Heart Failure. - Noma, Mounkaila; Khali, Siddig Ibrahim; Atabani, Suha Mahir; Homeida, Mamoun (Open Science Journal, 2017)
Background Idiopathic dilated cardiomyopathy (DCM) is a heart muscle disease of undefined cause that commonly presents as congestive cardiac failure. The etiology of weakness of the heart muscle is often unknown, but many causal factors had been identified. The aim of this study was to determine the prevalence and clinical presentations of dilated cardiomyopathy in Sudanese patients with heart failure. Method A prospective hospital-based observational study was undertaken during the period of January to April 2007 in two teaching hospitals namely Academy Charity Teaching Hospital and Shaab Teaching Hospital. All patients diagnosed by the physician to have heart failure were included in the study after their well informed consent and the consent of their treating physician. A standardized questionnaire developed by the researcher was used to collect data on patients socio-demographic characteristics, results of clinical, laboratory and radiography exams. All data were analyzed through the Statistical package for Social Sciences. Significance testing of difference between proportions was conducted using the Chi-square test were applicable, adjusted by Pearson's or Fisher's exact test, depending on the number of observations, with a value corresponding to p <0.05 for significance unless otherwise. Results Of the 72 patients in the study, 53.0% were males and 47.0% were females. The prevalence of DCM was found to be 43.1% (31 out of 72 heart failure patients). The prevalence was higher in males than females with a prevalence of respectively 47.4% and 38.2%. There was no significant difference in gender distribution of DCM (p=0.4). DCM affected older age with a mean age of 55.4 years (SEM=2.5). Palpitations, severe grade of dyspnea (grade 3 and 4), raised jugular venous pressure and cardiomegaly were the most frequent clinical presentations. The mean ejection fraction in DCM was found to be 36.7 (SEM=1.4). Conclusion Contrary to common belief among clinicians in Sudan DCM is one of the commonest causes of heart failure. Its prevalence called up a best practice among clinicians, in particular those practicing in emergency units.